Density functional studies of molecular polarizabilities. Part 2: Fulvene - Hinchliffe, Alan; Soscún, Humberto (Ciencia)
We report accurate Ab Initio studies of the dipole polarizabilities of fulvene at both the Hartree Fock HF and density functional (BLYP formulation) levels of theory. The molecular geometry was optimized with the following basis sets; STO-3G, 6-3 lG, 6-3 lG* and the dipole polarizability calculated with the corresponding geometry at both the HF and BLYP levels of theory. The molecular geometry was then optimized at the HF/6-311G(3d,2p) leve1 of theory, and dipole polarizabilities were calculated using this geometry using both HF and BLYP methods. The BLYP procedure gives small but significant differences from the corresponding HF results. We also give AMI, MNDO and PM3 polarizability calculations for comparison.